Avaliação da tendência à formação de fase vítrea nas ligas à base de alumínio do sistema Al-Y-Fe - Benavides Filho, Marcos Antonio (Universidade Federal de São Carlos, 2009)
The present work aimed to study the glass-forming ability of the aluminum-itrium-iron (Al-Y-Fe) alloys. The work included the preparation of samples through the melt-spinning technique and varying the composition of the samples. The structural characterization of the samples was made by x-ray diffraction technique (DRX) and differential scanning calorimetry (DSC). Some complementary characterizations included the Scanning Electron Microscopy (MEV) together with the Energy Dispersion Spectroscopy (EDS). Also were determinated the sample's characteristics temperatures liquidus temperature (Tliq), crystallization temperature (Tx) and glass-transition temperature (Tg). The glass-forming ability of the alloys was discussed based on different approaches from the literature . A discussion about the present glass-forming ability concept is put forward.
Keywords: Ligas de alumínio; Solidificação rápida; Tendência à formação de vidro; Ítrio; ENGENHARIAS